No benefit on functional outcomes and dislocation rates by increasing head size to 36 mm in ceramic-on-ceramic total hip arthroplasty - Yu-Der Lu; Shih-Hsiang Yen; Feng-Chih Kuo; Jun-Wen Wang; Ching-Jen Wang (Biomedical Journal, 2015)
Background: Ceramic-on-ceramic (COC) total hip arthroplasty (THA) has gained popularity since improvements in wear characteristics and longevity. Whether large ceramic femoral heads (≥36 mm) have increased postoperative range of motion (ROM) and a lower dislocation rate is not clear. This study aimed to compare functional outcomes and early complications between large-head (≥36 mm) and smaller-head (≤32 mm) COC prostheses with a minimum follow-up of 12 months. Methods: A total of 95 consecutive uncemented COC THAs were performed in 90 patients between January 2012 and July 2013. Of these, 49 patients (smaller-head group) received third generation and 41 patients (large-head group) received fourth generation COC prostheses. Harris hip score (HHS), Western Ontario and McMaster Universities Arthritis index (WOMAC), and ROM of the hip pre- and post-operatively were compared, as well as the presence of early complications. Results: Postoperative HHSs (88.4 vs. 89.3, p = 0.34) and WOMAC scores (12.0 vs. 11.0, p = 0.111) were not different between the groups. Postoperative flexion ROM was lower in the smaller-head group (98.8° vs. 106.1°, p < 0.001), but there were no differences in extension, abduction, adduction, internal rotation, and external rotation. One patient in each group reported a grinding noise. There was one dislocation (1.9%) in the smaller-head group, and none in the large-head group (p = 0.371). No infections or loosening of the components occurred. Conclusions: Large-head COC articulation provided better flexion, but functional outcomes and early complications are similar to the smaller-head COC.